Updates on NORA Musculoskeletal Health Cross-Sector Council Activities. (December 2020) - Rempel, David M.; Schneider, Scott; Gallagher, Sean; Gibson, Sheree; Kotowski, Susan; Lu, Ming- Lun; Fox, Robert R.; Dale, Ann Marie; Orr, Gary; Howard, Ninica; Zavitz, Ben; McGowan, Blake; et al.
The National Occupational Research Agenda (NORA) is a research framework for the nation and for the National Institute for Occupational Safety and Health (NIOSH). The NORA Musculoskeletal Health Cross-Sector (MUS) Council focuses on the mitigation of work-related musculoskeletal disorders (WMSDs). Two projects have been chosen by the MUS Council for disseminating existing information on ergonomic assessment methods and interventions. The first project involves collaboration with the AIHA Ergonomics Committee on the latest update of the AIHA Ergonomic Assessment Toolkit. The second project aims to post all-industry information on ergonomic solutions/interventions/guidelines in collaboration with the International Ergonomics Association (IEA). The MUS Council plans on leveraging the collaborative efforts for promoting widespread adoption of evidence-based workplace practices for the prevention of WMSDs.